Pengaruh Harga Dan Promosi Terhadap Kesadaran Merek Gojek Pada Pengguna Stasiun Kai Depok Baru - Kresna Wijaya; Dedik Supardiono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of Price and Promotion variables both partially and simultaneously on Brand Awareness of KAI Depok Baru Station users with a sample of 97 people. The method used is a quantitative method. Data analysis used in this study is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and F test. The results of this study are Price has a significant effect on Brand Awareness on the regression Y = 23.363 + 0.322 X1 correlation value of 0.377 meaning that the two variables have a low level of relationship. Promotion has a significant effect on Brand Awareness with the regression equation Y = 12.256 + 0.656 X2 correlation value of 0.690 meaning that the two variables have a strong level of relationship. Price and Promotion simultaneously have a significant effect on Purchase Interest with the regression equation Y = 9.477 + 0.108 (X1) + 0.618 (X2). The coefficient of determination value is 48.8%, while the remaining 51.2% is caused by other variables not examined in this study. The results of the first hypothesis test obtained a tcount value > ttable or (3.484 > 1.985). Based on the results of the second hypothesis test, the tcount value was obtained > ttable or (9.299 > 1.985). Based on the results of the third hypothesis test, the Fcount value was obtained > ftable (44.752 > 3.09). This shows that simultaneously the Price and Promotion variables have a significant influence on Brand Awareness.